2022 update to the position statement by Primary Care Diabetes Europe: a disease state approach to the pharmacological management of type 2 diabetes in primary care. Issue 2 (April 2022) - Seidu, S.; Cos, X.; Brunton, S.; Harris, S.B.; Jansson, S.P.O.; Mata-Cases, M.; Neijens, A.M.J.; Topsever, P.; Khunti, K.
Highlights: Primary care professionals face growing complexity of treatment options. This consensus recommends a simple, evidence-based CV risk stratification rubric. HCPs should consider early combination options for people with various comorbidities. A comprehensive summary of prescribing tips and side effects by drug class is given. Abstract: Type 2 diabetes and its associated comorbidities are growing more prevalent, and the complexity of optimising glycaemic control is increasing, especially on the frontlines of patient care. In many countries, most patients with type 2 diabetes are managed in a primary care setting. However, primary healthcare professionals face the challenge of the growing plethora of available treatment options for managing hyperglycaemia, leading to difficultly in making treatment decisions and contributing to treatment and therapeutic inertia. This position statement offers a simple and patient-centred clinical decision-making model with practical treatment recommendations that can be widely implemented by primary care clinicians worldwide through shared-decision conversations with their patients. It highlights the importance of managing cardiovascular disease and elevated cardiovascular risk in people with type 2 diabetes and aims to provide innovative risk stratification and treatment strategies that connect patients with the most effective care.